2021
DOI: 10.3389/fonc.2021.641980
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Cancer Organoids as Predictors of Treatment Response

Abstract: Patient-derived cancer organoids have taken a prominent role in pre-clinical and translational research and have been generated for most common solid tumors. Cancer organoids have been shown to retain key genetic and phenotypic characteristics of their tissue of origin, tumor subtype and maintain intratumoral heterogeneity and therefore have the potential to be used as predictors for individualized treatment response. In this review, we highlight studies that have used cancer organoids to compare the efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 88 publications
1
73
0
4
Order By: Relevance
“…It may be worthwhile to use newly developed techniques such as organoids [155,184] and xenografts [41] to measure cell type compositions and protein expression to monitor tumor evolution and improve our understanding of the eco-evolutionary dynamics. Early preclinical in vivo studies of adaptive therapy included ovarian cancer cell line xenografts treated with carboplatin, and MDA-MB-231/luc triple-negative and MCF7 ER+ breast cancer cell lines treated with paclitaxel.…”
Section: Clinical Relevancementioning
confidence: 99%
“…It may be worthwhile to use newly developed techniques such as organoids [155,184] and xenografts [41] to measure cell type compositions and protein expression to monitor tumor evolution and improve our understanding of the eco-evolutionary dynamics. Early preclinical in vivo studies of adaptive therapy included ovarian cancer cell line xenografts treated with carboplatin, and MDA-MB-231/luc triple-negative and MCF7 ER+ breast cancer cell lines treated with paclitaxel.…”
Section: Clinical Relevancementioning
confidence: 99%
“…This and other reviews have summarized that the 3D culture system of organoids can be established from almost all types of organs and allows improvement of fundamental understanding of disease onset and progression as well as of drug development and response prediction [ 5 , 7 , 8 , 11 , 99 , 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…To generate an overview of the current evidence on transferability of cancer organoid treatment results to the clinical setting, Verduin et al and Wensink et al conducted (systematic) reviews on the predictive value of tumor organoids [ 66 , 99 ]. Wensink et al showed that 5 out of 17 studies included in their systematic review reported a statistically significant correlation and/or predictive value and 11/17 at least a trend for a correlation or predictive value [ 66 ].…”
Section: Organoids As a Promising Tool For The Improvement Of Therapy Efficiency Predictionmentioning
confidence: 99%
“…A recent study showed that patient-derived organoid models can successfully predict sensitivity to chemotherapy and radiotherapy in patient with metastatic colorectal cancer [ 98 ]. An extensive review, which includes 60 studies in organoid research, indicated that organoid cultures are predictors of chemotherapy response in patients with different types of cancer [ 99 ].…”
Section: The Role Of Organoid Models and 3d Culture Systems In Chemosensitivity Assaysmentioning
confidence: 99%